Governance for Sustainable Development for Nickel Project in Indonesia - Muhammad Imam Akbar Hairi; Diki Zukriadi; Lingga Angling Wulung; Nur Elfi Husda (Magister Ilmu Administrasi Publik, 2023)
The paper investigates the governance and administrative process in the nickel project in Indonesia and offers suggestions to apply governance for sustainable development concept for creating an eco-mobility industry in Indonesia. This paper is a case study using qualitative methodology and governance for sustainable development theoretical framework. In applying qualitative methodology, this paper is supported by previous research publications, local press publications, and interviews. The governance for sustainable development is used as a strategic guideline in mining project to develop Indonesia’s eco-mobility industry further. This paper has three findings. First, the nickel project in Indonesia is part of bilateral cooperation between Indonesia with the National Strategic Program and China with the Belt and Road Initiative program. Thus, the concept of governance is not only applied in domestic policy but also bilateral cooperation. Second, non-technical issues have been identified during the governance and administrative process of nickel project in Indonesia. The governance concept must be applied to resolve the project’s non-technical problems and make it sustainable. Third, all the governance stakeholders in the nickel project must adopt a sustainable governance development framework. Indonesia should avoid further setback and refrain from the previous oil-booming phenomenon in the 1970s. The governance sustainable development concept requires all the stakeholders in the mining project to cooperate inclusively. It comprises extraction, production, recycling-waste management, e-vehicle industry, social acceptance, and rehabilitating the environment (land, air, water, and the living beings) affected by mining activities. This paper highlights Indonesia’s experience in creating an eco-mobility industry, using the nickel project as the key driver under investigation.